Unraveling the mechanisms of Sr35-based resistance in the wheat-Puccinia graminis f.sp. tritici pathosystem - Salcedo, Andrés Felipe (Kansas State University, 2018)
The fungus Puccinia graminis f. sp. tritici (Pgt) is the causal agent of the wheat stem rust disease. Wheat stem rust has attracted a lot of attention after the emergence of the Ug99 race group, which at the time of its origin was virulent on most of the wheat varieties cultivated around the world. The evolution and spread of the Pgt isolates from the Ug99 race group posed a serious threat to worldwide wheat production. To mitigate the potential impact of new rust epidemics in major wheat production areas, it remains critical to identify new strategies for breeding durable resistance traits. A detailed understanding of the plant-pathogen interaction mechanisms in the wheat-Pgt pathosystem should be the foundation of these strategies. The interaction between the matching pair of resistance (R) and avirulence (Avr) genes, an important element of the plant-pathogen interactions, is described by the broadly documented gene-for-gene model. The cloning of the Sr35 gene, which confers near immunity against all isolates from the Ug99 race group provided a unique opportunity to investigate the molecular mechanisms of resistance to stem rust in wheat. The goals of the present study were: (1) to determine whether the Sr35 gene alone is sufficient for conferring resistance against Ug99, (2) to assess the Sr35 transcript levels during the time course of infection, and (3) to identify and validate the corresponding Avr gene interacting with Sr35. The cloning of Avr genes from the biotrophic fungi represents a substantial challenge due to the variability, redundant nature, the lack of similarity to known proteins, and lack of adequate functional tools to validate them. To overcome these limitations, we performed a comparative genomic analysis using multiple Sr35-avirulent and Sr35-virulent races, including 15 chemically mutagenized Pgt strains that acquired virulence on the Sr35 gene. Whole genome shotgun sequencing of the Pgt mutants identified a single candidate gene, which carried strong effect mutations in each mutant strain. The Avr gene candidate (AvrSr35) was expressed at early stages of infection and had a signal peptide indicating that the gene product is secreted. Comparative microscopic analysis of the infected tissues at different time points after infection indicated that AvrSr35 secretion occurs before haustoria formation. The re-sequencing of the AvrSr35 candidate gene in a panel of Sr35-virulent and Sr35-avirulent isolates including isolates from the Ug99 race group, revealed the presence of a mobile DNA element inserted into the coding sequence of virulent isolates. This insertion resulted in a premature termination codon and explains the origin of Pgt field isolates virulent in the presence of the Sr35 gene. Co-expression of AvrSr35 with the Sr35 in N. benthamiana leaves induced a specific hypersensitive response confirming the avirulence function of the candidate effector gene. Subcellular localization, bi-molecular fluorescence complementation, and co-immunoprecipitation assays in N. benthamiana leaves revealed that the AvrSr35 and Sr35 proteins interact and are likely associated with the endoplasmic reticulum and plasma membrane. Thus, this study identified and functionally characterized the first matching pair of Avr/R genes for cereal rusts.
Keywords: Wheat; Stem rust; Avr-gene; R-gene; Fungal effector